Interactions of Potential Anti-COVID-19 Compounds with Multispecific ABC and OATP Drug Transporters - Ágnes Telbisz; Csilla Ambrus; Orsolya Mózner; Edit Szabó; György Várady; Éva Bakos; Balázs Sarkadi; Csilla Özvegy-Laczka (Pharmaceutics, 2021)
During the COVID-19 pandemic, several repurposed drugs have been proposed to alleviate the major health effects of the disease. These drugs are often applied with analgesics or non-steroid anti-inflammatory compounds, and co-morbid patients may also be treated with anticancer, cholesterol-lowering, or antidiabetic agents. Since drug ADME-tox properties may be significantly affected by multispecific transporters, in this study, we examined the interactions of the repurposed drugs with the key human multidrug transporters present in the major tissue barriers and strongly affecting the pharmacokinetics. Our in vitro studies, using a variety of model systems, explored the interactions of the antimalarial agents chloroquine and hydroxychloroquine; the antihelmintic ivermectin; and the proposed antiviral compounds ritonavir, lopinavir, favipiravir, and remdesivir with the ABCB1/Pgp, ABCG2/BCRP, and ABCC1/MRP1 exporters, as well as the organic anion-transporting polypeptide (OATP)2B1 and OATP1A2 uptake transporters. The results presented here show numerous pharmacologically relevant transporter interactions and may provide a warning on the potential toxicities of these repurposed drugs, especially in drug combinations at the clinic.